2019
DOI: 10.1111/cas.14074
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding‐RNA component of mitochondrial RNA processing endoribonuclease is involved in the progression of cholangiocarcinoma by regulating microRNA‐217

Abstract: Cholangiocarcinoma (CCA) is a malignant tumor originating from bile duct epithelium and its incidence is increasing year by year. In recent years, long noncoding RNAs (lncRNAs) have been found to play an important role in the occurrence and progression of malignant tumors. In the present study, for the first time, abnormal expression of lnc‐RNA component of mitochondrial RNA processing endoribonuclease (RMRP) and its possible role in CCA were found. We explored the effects of RMRP on various behaviors of CCA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Elevated levels of RMRP have been observed in different cancers, in one case as a result of transcriptional activation of the RMRP gene by the Wnt pathway through binding of YAP and β-catenin to the TATA box of the RMRP promoter (Park and Jeong 2015). High RMRP expression has been associated with poor patient prognosis and consistent with this, RMRP knockdown and overexpression experiments in various cancer cell lines revealed a positive role in cell proliferation and tumorigenic potential (Meng et al 2016;Shao et al 2016;Cao et al 2019;Hongfeng et al 2019;Pan et al 2019;Tang et al 2019;Wang et al 2019a,b;Xiao et al 2019).…”
Section: Rmrp In Cancermentioning
confidence: 82%
See 1 more Smart Citation
“…Elevated levels of RMRP have been observed in different cancers, in one case as a result of transcriptional activation of the RMRP gene by the Wnt pathway through binding of YAP and β-catenin to the TATA box of the RMRP promoter (Park and Jeong 2015). High RMRP expression has been associated with poor patient prognosis and consistent with this, RMRP knockdown and overexpression experiments in various cancer cell lines revealed a positive role in cell proliferation and tumorigenic potential (Meng et al 2016;Shao et al 2016;Cao et al 2019;Hongfeng et al 2019;Pan et al 2019;Tang et al 2019;Wang et al 2019a,b;Xiao et al 2019).…”
Section: Rmrp In Cancermentioning
confidence: 82%
“…In cholangiocarcinoma cells, knockdown of RMRP led to differential expression of 729 miRNAs as determined by high-throughput sequencing. Among them, miR-217, previously implicated in tumor suppression, was shown to contribute to the oncogenic potential of RMRP (Tang et al 2019). In multiple myeloma cells, a positive feedback loop consisting of c-Myc, RMRP, and miR-34a-5p was identified.…”
Section: Rmrp In Cancermentioning
confidence: 99%
“…Recently, lncRNAs have gained great attention as its role in CCA 15 . Several known lncRNAs were reported to be dysregulated in CCA tissues and involved in the CCA development and progression, such as DANCR 16 , PVT1 17 , and RMRP 18 . Recent studies have reported that SNHG6 is highly expressed in variety of cancer tissues (except CCA) and .…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs perform as antiregulators of gene expression (Giuliani et al, 2017). Interestingly, there are so many miRNAs that play an important role in the mitochondrial diseases and dysfunctions, for example, miR-122, miR-762, and miR-217 (Tang et al, 2019;Wang et al, 2019;Yan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%